2018
DOI: 10.1017/s0022149x18000160
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of human- and pig-derivedAscarisin Honduras

Abstract: Ascaris sp. is a soil-transmitted helminth (STH) significantly affecting the health of human and swine populations. Health inequities and poverty, with resulting deficiencies in water, sanitation and hygiene, are directly associated with Ascaris lumbricoides prevalence in humans. Resource constraints also lead to small-scale livestock production under unsanitary conditions. Free-ranging pigs, for instance, are exposed to a number of infectious agents, among which Ascaris suum is one of the most common. Under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Worms were thoroughly washed with a saline solution and stored at room temperature in 70% (v/v) ethanol until further use. DNA was purified using a previously described method 13 . Two separate PCR reactions were carried out to analyze three codons of the β-tubulin gene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Worms were thoroughly washed with a saline solution and stored at room temperature in 70% (v/v) ethanol until further use. DNA was purified using a previously described method 13 . Two separate PCR reactions were carried out to analyze three codons of the β-tubulin gene.…”
mentioning
confidence: 99%
“…Of the 50 adult Ascaris worms collected from 17 pigs, six (12%) had previously been classified as putative hybrids (or heterozygotes) between pig-and human-derived Ascaris through a PCR-RFLP approach of the nuclear internal transcribed spacer (ITS) ribosomal region 13 . The remaining 46 worms were classified as pig-derived Ascaris (Ascaris suum).…”
mentioning
confidence: 99%
“…Previous studies focused on endemic countries reported diverse patterns of genotypes, such as high level of cross-infections with A. suum in humans in China (Zhou et al, 2012); 9% of hybrids in pig-derived worms in Honduras (Palma et al, 2019); the absence of crosstransmission and the presence of A. lumbricoides in people and A. suum in pigs in Ecuador and Honduras (Sparks et al, 2015); very low percentage of A. suum in human samples from Zanzibar (Sparks et al, 2015), and pig-associated genotype in all samples from pigs and mainly human-associated genotype in samples from humans in Thailand, the Lao PDR, and Myanmar (Sadaow et al, 2018). The latter pattern is similar to the genotype distribution found in the present study in Colombia, here representative for the endemic countries.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Therefore, several studies have been conducted in countries such as Italy, Honduras, Brazil, Ecuador, Zanzibar, Myanmar, Thailand, and China (Cavallero et al, 2013;Monteiro et al, 2019;Palma et al, 2019;Sadaow et al, 2018;Sparks et al, 2015;Zhou et al, 2018), aiming to evaluate the amount and nature of genetic diversity of Ascaris spp. circulating in humans and pigs, and to explore their zoonotic potential and cross-transmission.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, rustically reared pigs are housed in a pigsty, usually a roofed, dirtfloor structure; other less well-delimited areas, with or without walls, are sometimes used as pigsties. Pig feed may consist of grains and food waste, but rustically reared pigs obtain most of their diet by foraging through the village or its surroundings (Linares-Ibáñez et al, 2011;Thomas et al, 2013;Palma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%